Scientific-Based Animation Media for Elementary Plant Reproduction Education: A Comprehensive Needs Analysis - Purdianto, Timan; Susanti, L R Retno; Safitri, Erna Retna (Journal of Innovation and Research in Primary Education, 2025)
The use of animation media in science education offers significant potential for presenting abstract concepts in more concrete and comprehensible ways. This study aimed to identify the needs for developing scientific-based animation media on generative plant reproduction materials in elementary schools. Employing a Research and Development (R&D) approach with the 4D model (Define, Design, Develop, Disseminate), this study involved 60 elementary students and five science teachers in Palembang, Indonesia. Data were collected through validated questionnaires assessing academic needs, technology needs, and pedagogical requirements, and analyzed using descriptive statistics. Results revealed that students demonstrated strong preferences for visual learning materials (71.7%) and play-based learning activities (75.0%), with exceptionally high demand for technology integration (81.7%). Teachers possessed adequate pedagogical competence but faced significant infrastructure constraints. The average scores for student academic needs (64.9%) and technology needs (66.1%) indicated moderate to high requirements for innovative learning media. These findings confirm that scientific-based animation media represents a necessary solution for addressing educational gaps in teaching abstract biological concepts. The study contributes empirical evidence supporting animation media development through comprehensive dual-stakeholder analysis, providing valuable insights for educators, curriculum developers, and policymakers in enhancing elementary science education through technology-integrated instruction.